Pendidikan Karakter Berbasis Budaya Sebagai Solusi Degradasi Bangsa - I Made Ariasa Giri (Purwadita : Jurnal Agama dan Budaya, 2020)
Education is a planned effort to develop the potential of students, so that they have a system of thinking, a system of values, morals, and beliefs inherited by their communities to develop according to life in the present and the future. While the character is the character, character, character, or personality of a person formed from the internalization of various virtues (virtues) that are believed and used as a basis for perspective, thinking, acting and acting. these character education development strategies have principles that are used so that character education can run effectively. The principles are sustainable, through all subjects, personal development, and school culture and values are not taught but are developed. The character education that is developed stems from the basic values contained in the principles of the Pancasila and from the daily values that grow in a civilized society. With the existence of character education, can develop the spirit of leadership, responsibility, honesty, creative and cultured in each student so that the goals of character education can run perfectly. Keywords: Character Education, Culture, Nation degradation